Application of Educational Psychology Principles Encourages Student Engagement in the Learning Process - Makmun, Sukron; Amar, Muh.; Zainudin; Isral Ayubi, Adim; Risti Puji Lestari, Nadila (International Journal of Education and Digital Learning (IJEDL), 2025)
This study aims to describe the application of educational psychology principles at SMPN 3 Central Praya and the perceptions of teachers and students towards its application. This descriptive qualitative study with a case study design involved teachers and students as research subjects, focusing on teachers who actively apply educational psychology principles and students who feel the impact. Data collection was carried out through surveys, in-depth interviews, observations, and documentation, then analyzed through data reduction, data presentation, and drawing conclusions. The results of the study showed the commitment of teachers in creating effective and student-centered learning, reflected in the recognition of the diversity of learning styles, the connection of material with the context of life, and the creation of a conducive learning environment. Problem-based and project-based learning methods and cooperative learning were considered effective. Teachers and students had positive perceptions towards the application of these principles, indicated by increased learning motivation, understanding of the material, active participation, and positive interactions between teachers and students. Thus, the findings of this study confirm that the application of the principles of educational psychology has a positive impact and is a strong foundation for improving the quality of learning at SMPN 3 Central Praya.